Experimental determination and analysis of gold nanorod settlement by differential centrifugal sedimentation. Issue 49 (3rd May 2016) - Wang, Ruimin; Ji, Yinglu; Wu, Xiaochun; Liu, Renxiao; Chen, Lan; Ge, Guanglu
Abstract : Direct measurement of the sedimentation coefficients of gold nanorods with a controlled shape factor was performed using differential centrifugal sedimentation (DCS). Abstract : Direct measurement of the sedimentation coefficients of gold nanorods with a controlled shape factor was performed using differential centrifugal sedimentation (DCS). The results serve as a testing ground for various existing models describing non-spherical nanoparticles moving in a centrifugal field based on sphericity and force analysis, and point to further refinement.